Uterine secretome: What do the proteins say about maternal-fetal communication in buffaloes? - Codognoto, Viviane Maria [UNESP]; de Souza, Fabiana Ferreira [UNESP]; Cataldi, Thais Regiani; Labate, Carlos Alberto; de Camargo, Laíza Sartori [UNESP]; Scott, Caroline [UNESP]; da Rosa Filho, Roberto Rodrigues; de Carvalho, Nélcio Antonio Tonizza; Oba, Eunice [UNESP] (Elsevier, 2024)
The aim was to compare the UF proteomics of pregnant and non-pregnant buffalo during early pregnancy. Forty-four females were submitted to hormonal estrus synchronization and randomly divided into two groups: pregnant (n = 30) and non-pregnant (n = 14). The pregnant group was artificially inseminated and divided into a further two groups: P12 (n = 15) and P18 (n = 15). Conceptus and uterine fluid samples were collected during slaughter at, respectively, 12 and 18 days after insemination. Of all the inseminated females, only eight animals in each group were pregnant, which reduced the sample of the groups to P12 (n = 8) and P18 (n = 8). The non-pregnant group was also re-divided into two groups at the end of synchronization: NP12 (n = 7) and NP18 (n = 7). The UF samples were processed for proteomic analysis. The results were submitted to multivariate and univariate analysis. A total of 1068 proteins were found in the uterine fluid in both groups. Our results describe proteins involved in the conceptus elongation and maternal recognition of pregnancy, and their action was associated with cell growth, endometrial remodeling, and modulation of immune and antioxidant protection, mechanisms necessary for embryonic maintenance in the uterine environment. Significance: Uterine fluid is a substance synthesized and secreted by the endometrium that plays essential roles during pregnancy in ruminants, contributing significantly to embryonic development. Understanding the functions that the proteins present in the UF perform during early pregnancy, a period marked by embryonic implantation, and maternal recognition of pregnancy is of fundamental importance to understanding the mechanisms necessary for the maintenance of pregnancy. The present study characterized and compared the UF proteome at the beginning of pregnancy in pregnant and non-pregnant buffaloes to correlate the functions of the proteins and the stage of development of the conceptus and unravel their processes in maternal recognition of pregnancy. The proteins found were involved in cell growth and endometrial remodeling, in addition to acting in the immunological protection of the conceptus and performing antioxidant actions necessary for establishing a pregnancy.
Keywords: Maternal recognition of pregnancy; Proteomics; Uterine fluid